Overdetermined problems for p-Laplace and generalized Monge–Ampére equations - Emamizadeh, Behrouz; Liu, Yichen; Porru, Giovanni (2020)
We investigate overdetermined problems for p-Laplace and generalized Monge-Amp´ere equations. By using the theory of domain derivative we find duality results and a characterization of the overdetermined boundary conditions via minimization of suitable functionals with respect to the domain.